Effects of COVID-19 on Mental Health and Anxiety of Adolescents Aged 13–16 Years: A Comparative Analysis of Longitudinal Data From China - Qin, Jie; Ding, Yueyue; Gao, Jing; Wu, Yun; Lv, Haitao; Wu, Jian (Frontiers in Psychiatry, 2021)
Background: Adolescence is an important stage of psychological development, and the psychological and mental problems of many adults are affected by the COVID-19 epidemic. The aim of this study was to understand the psychological status of this group during the epidemic, and to determine the risk factors leading to psychological stress, as well as protective factors. Methods: An online survey was run on April 2, 2020. The participants were 254 adolescents aged 13-16 years from a junior high school in Jiangsu, China. The results were compared with the pre-epidemic data, which came from the psychological status survey routinely carried out by the school. Mental health variables were assessed via the Mental Health Test that included one validity subscale and eight content subscales. Results: The number of adolescents with poor mental health increased significantly from 12.3% to 24.2%. There was significant increase in learning anxiety (33.7 vs. 56.4%), sensitivity tendency (19.8 vs.46%), somatic anxiety (13.9 vs. 40.7%) and phobia tendency (4.4 vs. 10.1%). During the epidemic, there were significant differences between adolescents with normal and poor mental health in family structure, personality, relationship with siblings, daily exercise time, and risk of family members coming in contact with COVID-19. Living in stem family, no siblings, and risk of contracting COVID-19 from family members were significant risk factors for teenagers with poor mental health. Risk of contracting COVID-19 from family members was the most influential risk factor for learning anxiety, self-blaming tendency, sensitivity tendency and somatic anxiety. Exercising for ≥1 hour per day was a significant protective factor for poor mental health. Conclusions: During the COVID-19 epidemic, adolescents aged 13-16 years have had psychosocial problems, especially learning anxiety, sensitivity tendency, somatic anxiety and phobia tendency, as well as risk factors for developing them. Our study provides insights for potential interventions.